Greeffiella bellula n. sp. (Nematoda: Desmoscolecida): The First Desmoscolecid Nematode Species to Be Described From New Zealand - Daniel Leduc; Zeng Qi Zhao (New Zealand Journal of Marine and Freshwater Research, 2026)
The mostly marine nematode order Desmoscolecida is globally distributed with over 270 species known to date. Here, we describe Greeffiella bellula n. sp., the first desmoscolecid species to be described from New Zealand waters, from deep‐sea sediments. The new species is most similar to G. japonica , described from coastal sediments in the Sea of Japan, in having relatively few ( Greeffiella bellula n. sp. can be most easily differentiated from the latter by the different body shape and in having fewer pairs of subdorsal setae. A dichotomous key to the 15 valid species of the genus is presented. Results of SSU phylogenetic analyses based on 19 Desmoscolecidae sequences confirmed the genus assignment of the new species, but unlike previous analyses did not provide support for the monophyly of the subfamilies Desmoscolecinae and Tricominae, or of the closely related genus Desmoscolex .